Copper-Free Double Silylation of 1,2-Dibromobenzenes Using a Mg/LiCl/DMI System - Kitamura, Tsugio; Yamada, Rin; Gondo, Keisuke; Eguchi, Nobuo; Oyamada, Juzo (Synthesis, 2017)
The reaction of 1,2-dibromobenzenes with chlorotrimethylsilane efficiently proceeded in the presence of Mg and LiCl in DMI under mild conditions, giving 1,2-bis(trimethylsilyl)benzenes in good to high yields. The reaction of 1,2-dibromobenzenes with chlorodimethylsilane under the same conditions afforded the corresponding 1,2-bis(dimethylsilyl)benzenes in high yields. Functional group transformations of 1,2-bis(trimethylsilyl)benzene were conducted to demonstrate the synthetic utility.
Keywords: copper-free reaction; double silylation; 1,2-bis(trimethylsilyl)benzenes; mild conditions; 1,2-dibromobenzenes; Mg/LiCl/DMI system